PRIORITY AREAS FOR THE DEVELOPMENT OF LIFE INSURANCE IN UZBEKISTAN (Лучшие интеллектуальные исследования, 2025)
ABSTRACT: The article provides information on the definition of life insurance and its main features, as well as its role in social protection. As a result of the abolition of tax benefits related to life insurance, an analysis of insurance premiums received in the life insurance industry under the influence of a decrease in insurance demand has been conducted, and proposals and recommendations for its development have been developed.